Spouting, a new technique in coating - Haseeb, Kanwar Abdul 1936-
The use of the moving air mass principle in pharmaceutical operations specifically those related to tablet manufacturing, has been reported in the literature with increasing frequency since the report of D.E. Wurster in 1959. In spouting, a central cone of particles whose apex is located at the gas inlet is entrained in the rising air mass. When the velocity of the air mass becomes sufficiently high, a sharply bounded stream of particles is projected upwards through a channel terminating a jet of gas and solids. The solids enter the channel mainly in the base section. However, solids also move from higher strata laterally into the channel. At the upper end of the channel, the solids spill over radially into the annulus that defines a column of descending solids. In this investigation, spouting has been applied successfully in coating of tablets, and an equipment based on the principle has been constructed which consists of a cylindrical chamber 6" in diameter and about 4 feet in height. The base is provided with an inclined grid whose cross section may be described as a shallow trough. Below the grid is the source of moving air mass which provides the force necessary for the propulsion of the solid particles. In operation, the cylinder is charged with the solid particles up to about a height of 4-6 inches as measured from the lowest section of the grid. The jetted particles move across the breadth of the chamber and drop onto the far side of the upper surface of the bed. The cycle is repeated for each particle by having it move laterally at a slant toward the channel. The inclined grid which has a shallow trough cross-section, aids greatly in attaining a well-defined oval pattern in which all of the tablets are involved uniformly. The coating solution is applied from the top of the cylinder by means of a spray nozzle. By the use of this equipment, tablet coating had been finished within 20-30 minutes reducing the coating time appreciably.